2014
DOI: 10.3109/02770903.2014.999284
|View full text |Cite
|
Sign up to set email alerts
|

Early-life antibiotic use is associated with wheezing among children with high atopic risk: a prospective European study

Abstract: In European children with a familial risk for allergic sensitization, we found a positive association between macrolide use in the first year of life and wheezing until 36 months old which was independent of the effect of respiratory infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…In our study population, a large proportion of infants were exclusively breastfed for the first 6 months. In addition, the median duration of breastfeeding was 10.5 months, which more closely matches the population studied by Kopp et al 6 Given the multitude of factors that may affect the risk of allergic disease, the effect of supplementation with a single probiotic species may only be discernable in high-risk infants who are also born into high-risk scenarios because of altered gastrointestinal microbiota development (eg, cesarean delivery, early broad spectrum antibiotic exposure, 28,29 and perhaps lack of breast milk exposure).…”
Section: Figuresupporting
confidence: 73%
“…In our study population, a large proportion of infants were exclusively breastfed for the first 6 months. In addition, the median duration of breastfeeding was 10.5 months, which more closely matches the population studied by Kopp et al 6 Given the multitude of factors that may affect the risk of allergic disease, the effect of supplementation with a single probiotic species may only be discernable in high-risk infants who are also born into high-risk scenarios because of altered gastrointestinal microbiota development (eg, cesarean delivery, early broad spectrum antibiotic exposure, 28,29 and perhaps lack of breast milk exposure).…”
Section: Figuresupporting
confidence: 73%
“…children who received antibiotics have higher incidence of allergy and asthma [3133]. Besides these seemingly negative effects on immune development, one can imagine that it may also be possible to positively modulate immune development by providing specific diets or feed additives that influence the microbial colonization of the gut.…”
Section: Discussionmentioning
confidence: 99%
“…74,75 Similar studies on full term infants receiving perinatal antibiotics also showed that antibiotic treatment as associated with less bacterial diversity along with higher proportions of Proteobacteria and Enterobacteriaceae and lower proportions of Bifidobacterium and Lactobacillus (Table 1). 76,77 When considering the relationship between the development of allergic disease and early-life antibiotic exposure, there appears to be an association between both prenatal 78,79 and postnatal 7981 antibiotic exposure and asthma. It should be noted, however, that many studies might be confounded by an increased treatment of respiratory infections at an early age when manifestations of asthma may be indistinguishable from infection.…”
Section: The Influence Of the Microbiome In Allergic Diseasementioning
confidence: 99%